What makes one feel eustress or distress in quarantine? An analysis from conservation of resources (COR) theory. Issue 2 (5th January 2021) - Merino, M. Dolores; Vallellano, M. Dolores; Oliver, Coral; Mateo, Inmaculada
Abstract : Objective: Health quarantines produce serious deterioration in psychological health, which becomes more affected the longer the quarantine lasts. According to the Conservation of Resources theory from Hobfoll (1989, American Psychologist, 44, 513), those people who have a good supply of resources will be able to cope better with the adversities and will show less distress. The objective of this research is to identify what are the resources that, in a situation of confinement under the threat of COVID‐19, predict eustress or well‐being, and the loss or lack of which resources predict distress or discomfort. Design and Method: A total of 839 people complete an online questionnaire during the first week of COVID‐19 confinement in Spain. The sample is weighted to obtain a distribution that is similar to the Spanish population. Using multiple linear regression analysis, factors are identified that are associated with eustress and distress based on the Conservation of Resources theory. Results: A model is identified that explains 55% of the variance of eustress consisting mostly of personal resources, with vitality as the recourse having the most weight. The factors that explain distress (18.9% of the variance) are those related to work (employment situation, work satisfaction, and time devoted to work) and conditions in the home (space). Conclusions: The models that predict eustress and distress are completely different. Based on these results, a series of recommendations are proposed aimed at increasing eustress and reducing distress in a situation of confinement. Additionally, proposals are offered for future research.